The Effect of Aqueous Extract Cinnamon Zeylanicum Bark on the Structure and Function of the Ovary in Female Rats - Enas Waleed Shakir Al-Najjar (College of Pharmacy / Mustansiriyah University, 2011)
The effect of aqueous extract cinnamon zeylanicum bark on the structure and function of ovary was studied for the females of rats physiologically and histological. Number of (20) white rats were used for this study, divided into two groups that treated as follows: The first group is the control group that have got the regular water and food, while the second group has have been treated with the aqueous extract cinnamon bark of concentration 5 mg/ml for a period of 15 days. The histological study for the aqueous cinnamon bark extract treated group showed that the existence of the Primary follicles, Preantral follicles and in addition to a number of Corpora lutea that indicates the occurring of ovulation comparing with the control group that showed only the Primoridail follicles which reflects the effect of the cinnamon on the ovary activity. The hormonal study shows also a significant increment (P<0.01) in the levels of Progesterone, Estridiol, LH, and FSH in the treated groups comparing with the control group. The results of this study indicates the ability of the cinnamon plant to stimulate secretion of the gonadotropin and hence the activity of the ovary.